Antidiabetic plants improving insulin sensitivity. (15th April 2014) - Eddouks, Mohamed; Bidi, Amina; El Bouhali, Bachir; Hajji, Lhoussain; Zeggwagh, Naoufel Ali
Abstract: Background: Globally, the prevalence of diabetes mellitus is increasing at an alarming rate. This chronic pathology gravely troubled the human health and quality of life. Both insulin deficiency and insulin resistance are involved in the pathophysiology of diabetes mellitus. Moreover, insulin resistance is being diagnosed nowadays in a growing population of diabetic and obese patients, especially in industrialized societies. There are lots of conventional agents available to control and to treat diabetes, but total recovery from this disorder has not been reported up to this date. Plants provided a potential source of hypoglycemic drugs and are widely used in several traditional systems of medicine to prevent diabetes. A few reviews with less attention paid to mechanisms of action have been published on antidiabetic plants. Objectives: The present review focuses on the various plants that have been reported to be effective in improving insulin sensitivity associated with diabetes. Key findings: In this work, an updated systematic review of the published literature has been conducted to review the antidiabetic plants improving insulin sensitivity and 111 medicinal plants have been reported to have a beneficial effect on insulin sensitivity using several in-vitro and in-vivo animal models of diabetes. Conclusion: The different metabolic and cellular effects of the antidiabetic plants improving insulin sensitivity are reported indicating the important role of medicinal plants as potential alternative or complementary use in controlling insulin resistance associated with diabetes mellitus.